2019
DOI: 10.3389/fnmol.2019.00218
|View full text |Cite
|
Sign up to set email alerts
|

Gut Inflammation in Association With Pathogenesis of Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is a neurodegenerative disease that is generally thought to be caused by multiple factors, including environmental and genetic factors. Emerging evidence suggests that intestinal disturbances, such as constipation, are common non-motor symptoms of PD. Gut inflammation may be closely associated with pathogenesis in PD. This review aims to discuss the cross-talk between gut inflammation and PD pathology initiation and progression. Firstly, we will highlight the studies demonstrating how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 179 publications
(217 reference statements)
2
55
2
Order By: Relevance
“…Epidemiological investigations also found that non-steroidal anti-inflammatory drugs (NSAIDs) are related to a lower risk of developing PD (Noyce et al, 2012), suggesting that neuroinflammation may promote disease progression. In addition, emerging evidence demonstrates that intestinal inflammation may also be involved in PD pathophysiology through the regulation of the gut-brain axis (Chen et al, 2019). We found that the TNF signaling pathway is a key pathway of P. lactiflora for PD.…”
Section: Paeonia Lactiflora May Contribute To the Treatment Of Parkinmentioning
confidence: 70%
“…Epidemiological investigations also found that non-steroidal anti-inflammatory drugs (NSAIDs) are related to a lower risk of developing PD (Noyce et al, 2012), suggesting that neuroinflammation may promote disease progression. In addition, emerging evidence demonstrates that intestinal inflammation may also be involved in PD pathophysiology through the regulation of the gut-brain axis (Chen et al, 2019). We found that the TNF signaling pathway is a key pathway of P. lactiflora for PD.…”
Section: Paeonia Lactiflora May Contribute To the Treatment Of Parkinmentioning
confidence: 70%
“…The influence of the gut microbiota in the context of PD has recently become an intense area of preclinical research [45] and this has given rise to a number of clinical trials targeting dysbiosis in the gastrointestinal system. There were five studies seeking to positively influence the content and activity of gut microbiota, all of which were under way in academic institutions.…”
Section: Disease-modifying Therapiesmentioning
confidence: 99%
“…Apart from α-synuclein mediated activation of microglia in the CNS, a more complex relationship between gut microbial-induced inflammation and α-synuclein expression and aggregation has been proposed to occur in the periphery (Chen S.G.et al, 2016;Choi J.G.et al, 2018). Clinical, epidemiological and animal studies suggest a complex cross-talk between intestinal inflammation and PD pathology initiation and progression (Houser and Tansey, 2017;Chen et al, 2019). Similarly, α-synuclein-evoked microglial activation is commonly detectable in the brains of MSA patients (Ishizawa et al, 2004) and MSA experimental models (Stefanova et al, 2007;Vieira et al, 2015;Monzio Compagnoni and Di Fonzo, 2019).…”
Section: α-Synuclein As the Primary Culprit For Synucleinopathiesmentioning
confidence: 99%
“…et al, 2018 ). Clinical, epidemiological and animal studies suggest a complex cross-talk between intestinal inflammation and PD pathology initiation and progression ( Houser and Tansey, 2017 ; Chen et al, 2019 ). Similarly, α-synuclein-evoked microglial activation is commonly detectable in the brains of MSA patients ( Ishizawa et al, 2004 ) and MSA experimental models ( Stefanova et al, 2007 ; Vieira et al, 2015 ; Monzio Compagnoni and Di Fonzo, 2019 ).…”
Section: α-Synuclein As the Primary Culprit For Synucleinopathiesmentioning
confidence: 99%